Elevational adaptation and distribution of woody saplings in a mountain forest: Insights from functional traits and mycorrhizal associations - Zuhua Wang; Xia Cai; Min Liu; Haibo Li; Jiayan Jiang; Jugang Wang; Fagen Qiu (Global Ecology and Conservation, 2025)
A trait-based approach can be used to effectively elucidate the adaptive strategies of trees in response to climate change, although the strategies of saplings remain unclear. Therefore, the adaptative strategies of saplings and the relative contributions to their elevational distribution were detected. Eight leaf-absorptive root traits of 163 individuals across 41 saplings were investigated, and the soil properties and climate factors were also investigated along an elevational gradient on Mt. Fanjingshan, Tongren, Guizhou, China. Principal component analysis revealed three key dimensions of trait variation: (1) the root economics spectrum, explaining 33 % of variation; (2) the leaf economics spectrum, explaining 28 %; and (3) the root collaboration gradient, explaining 17 %. Notably, ericoid mycorrhizal species exhibited more acquisitive root strategies (higher specific root length and specific root area) than arbuscular mycorrhizal and ectomycorrhizal species, while arbuscular mycorrhizal species showed more acquisitive leaf traits (higher specific leaf area and leaf N). Along the elevational gradient, arbuscular mycorrhizal species shifted toward acquisitive root traits, ectomycorrhizal species developed thinner roots, and ericoid mycorrhizal species displayed a unique dual strategy - increasing root acquisitiveness while maintaining conservative leaf traits. Soil properties, particularly temperature and nitrogen availability, were the primary drivers of trait variation and sapling distribution, explaining 79–83 % of elevational variation. Our results demonstrate that mycorrhizal type fundamentally influences trait coordination, with plants exhibiting distinct whole-plant strategies along environmental gradients. These findings highlight the importance of incorporating mycorrhizal associations when predicting plant responses to environmental change.